تصميم وتقويم تطبيق أي-كلام لتعلّم مهارة الكلام باللغة العربية: تحليل الحاجات نموذجا = Design and evaluation of i-Kalam application for learning Arabic speaking skill: a need analysis - Abdullah, Alif Fahmi; Ismail, Taufik; Sahrir, Muhammad Sabri; Mohd Abd Shukur, Mohd Izzat (Penerbit Universiti Sains Islam Malaysia (USIM), 2024)
Smartphones are part of the modern learning tools that play an important role in helping students during language learning, and are considered effective educational devices for learning the Arabic speaking skill. Studies have revealed that students find it difficult to practice speaking at school, at home, and in daily interactions with others. This study is aimed to identify the needs of Arabic language learners in designing the i-Kalam application for strengthening Arabic speaking skill among religious secondary school students. Unified Theory of Acceptance and Use of Technology (UTAUT) theory were used as a basic model for the study. A survey method was utilized among 105 Form One students at Sekolah Menengah Agama Al-Madrasah Ad-Diniah Al-Alawiyah in Arau, Perlis. The data obtained were analyzed through descriptive statistics using the Statistical Packages for the Social Sciences (SPSS) software. The overall findings show a high need to design an application to strengthen the Arabic speaking skill. The students believe that using a smartphone application is able to increase their opportunities to practice speaking in Arabic. The results also indicate that the students love and enjoy learning the Arabic speaking skill using the smartphones application.